Survey on Storage Insect Pest, Methods of Storage and Management Measures on Sorghum Grain around Sub Zoba Hamelmalo, Eritrea - Sethumadhava Rao, Mulue Girmay Ruta Tewelde (International Journal of Scientific Research and Management (IJSRM), 2017)
Survey was intended to study the storage insect pests in sorghum around the sub-zoba Hamelmalo. Though this crop is one of the most stable field crops in Eritrea, it is severely infested by many storage insect pests. Therefore, the survey was conducted to address the challenges with storage insect pests with the aim of identifying the storage insect pests of sorghum grains, storage methods of the subsistence farmers and its management practices used by the farmers. The survey was carried out in sub-zoba Hamelmalo by using open ended questionnaires. Five administrative villages were randomly selected and from each village eleven farmers were selected at random for interview and sample collections. Five hundred gram of sorghum grains were collected and checked for pest occurrence and emergence in the laboratory. Sitophilus oryzae, Sitotroga cerealella and Sitophilus granaries were recognized as major storage insect pests in the representative administrative villages. The study discovered that the weight losses due to the storage insect pests range from 0.089% to 1.82% in sub-zoba Hamelmalo. The interview showed farmers in the sub-zoba used different management practices including ash mixing with grain, sun drying, cleaning, plant materials and insecticides to protect the grain from storage insect pests. In addition to that it is indicated that the most of the growers of the sampled villages used polyethene (meshemae) and guffet (traditional storage material) to store their produce.